ICU survivors' utilisation of diaries post discharge: A qualitative descriptive study - Ewens, B.; Chapman, Rose; Tulloch, A.; Hendricks, J. (2014)
Background: A growing body of evidence has confirmed that intensive care unit survivors encounter myriad of physical and psychological complications during their recovery. The incidence of psychological morbidity in intensive care survivors is increasingly being recognised. The causes of psychological morbidity are multi-factorial but may be associated with a complete lack of, or delusional recall of events in intensive care. Intensive care unit diaries are an initiative designed to enable survivors to help restore factual memories and differentiate those from delusional. Purpose: To explore survivors' and family members' perceptions and utilisation of diaries following discharge from hospital. Method: A single centre qualitative descriptive study was undertaken in a general intensive care unit in Western Australia. Participants were surveyed 3, 6 and 12 months following discharge from hospital. Eighteen participants completed one or more surveys. Findings: Many of the participants who completed the surveys read their diaries but few made entries in them following discharge. Reading the diaries evoked mixed emotions for these participants; however they still viewed the diaries as a positive initiative in their recovery. Diaries enabled survivors to fill the memory gaps, make sense of their experience and reinforced the human connection when they were immersed in a technological environment. Conclusion: Use of patient diaries was received positively by the participants in this study. Diaries are a simple, cost effective initiative which enabled survivors to piece together the time they had lost, concreted their experience in reality and enabled them to retain a connection with their loved ones whilst immersed in a technological environment.